Ocena żyzności gleb intensywnie użytkowanych za pomocą wartości indeksu trofizmu gleb leśnych = The evaluation of fertility of intensively cultivated soils on the base of forest soil trophism index - Mikiciuk, Grzegorz; Tomaszewicz, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this research was evaluation of soils in experimental station in Dołuje as forest habitat basing on the forest soil trophism index (FSTI). The studied soils were classified as IVa quality class and were intensively cultivated. The values of FSTI, helped to determine them as hypertrophic forest habitat.
Keywords: czarne ziemie; gleba murszasta; uziarnienie; właściwości chemiczne; indeks trofizmu gleb leśnych (ITGL); black earth; mucky soils muckous; soil texture; chemical properties; Forest Soil Trophism Index (FSTI)